Review and analysis of wind and solar PV farms power outputs to meet Ontario hourly electricity demand with optimal sizing of PV farms, wind farms, and energy storage systems - Fong YeeNok; Fung Alan S. (E3S Web of Conferences)
This study explores the feasibility of eliminating natural gas-based power generation from Ontario’s power grid by focusing on integrating renewable energy sources such as solar and wind energy. Due to the weather dependent nature of these energy sources, the integration of energy storage systems (ESS) into the power grid was also examined to ensure grid stability. Two types of ESS examined were the battery energy storage system (BESS) and pumped hydroelectric storage (PH). The analyses founds that the most cost-effective power generation configuration is to expand the current wind energy generation to 4 times of its current size, solar energy to 5.67 times, nuclear energy to 1.1 times and utilize 289 BESS units. Moreover, a 3-year long continuous analysis was performed to assess the configuration’s long-term stability and its adaptability to change in demand, it was found that BESS is better suited for wind energy due to its faster response time while solar energy favors PH as the energy storage solution due to having larger storage capacity.